Integrating Mobile Health with Islamic Psychospiritual: Digital Approaches to Psychological and Spiritual Well-Being - Ahmad Syahir, Aminun Nabil; Zainal Abidin, Mohd Syukri; Sa'ari, Che Zarrina; Mukaffa, Zumrotul (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The rise of mobile health technologies has created new pathways for enhancing psychological and spiritual well-being. This research examines how mHealth can be aligned with Islamic psychospiritual principles to offer a comprehensive approach to mental health. By integrating digital solutions with Islamic values, mHealth applications can provide tailored mental health support and enhance spiritual resilience. Yet, these new technologies present concerns such as ethical management, safeguarding data privacy, and the risk of trivializing spiritual practices. This study examines these issues while showcasing the potential of mHealth as a means to connect traditional healthcare with faith-centered methods. The research highlights the need for appropriate digital strategies that engage religious leaders, policymakers, and mental health experts. Further studies should aim to create genuine, trust-centric frameworks that support accessibility, inclusivity, and responsible application of technology. Effectively merging mHealth with Islamic psychospiritual principles can transform mental health support, promoting a balanced and meaningful sense of well-being within Muslim communities across the globe.